False resistance after artemether–lumefantrine treatment in a falciparum malaria patient in Turkey: A case report. (2019) - Koru, Ozgur; Yazici, Ertugrul; Rasmussen, Charlotte; Ringwald, Pascal; Artuk, Cumhur; Bedir, Orhan
Abstract: Introduction: Artemisinin-based combination therapy (ACT) is recommended by the World Health Organization as first-line treatment of uncomplicated Plasmodium falciparum malaria. ACT treatments failures among travellers returning from Africa to non-endemic countries are considered to be caused by resistance. Case presentation: We report on a case of artemether-lumefantrine treatment failure in a Turkish traveller with uncomplicated P. falciparum malaria returning from Bamako, Mali. Conclusions: Information on returning travellers, includes ensuring that the patients receive supervised treatment with the recommended dose of a quality controlled medicine, routine follow-up of all cases, assessment of adequate absorption of the drug, and/or testing the prevalence of molecular markers of drug resistance if validated, can be an important source of an early warning system for emerging resistance.